2017
DOI: 10.1002/jbm.a.36033
|View full text |Cite
|
Sign up to set email alerts
|

Continuous microfluidic assembly of biodegradable poly(beta‐amino ester)/DNA nanoparticles for enhanced gene delivery

Abstract: Translation of biomaterial-based nanoparticle formulations to the clinic faces significant challenges including efficacy, safety, consistency and scale-up of manufacturing, and stability during long-term storage. Continuous microfluidic fabrication of polymeric nanoparticles has the potential to alleviate the challenges associated with manufacture, while offering a scalable solution for clinical level production. Poly(beta-amino esters) (PBAE)s are a class of biodegradable cationic polymers that self-assemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…This heterogeneity can be exacerbated by scaling up from small scale bulk mixing conditions found in a laboratory to larger size volumes, especially as mixing environments vary with different types of processing equipment. To help alleviate these concerns, increasing attention in the nanomedicine field has turned to continuous manufacture processes such as microfluidic mixing and extrusion techniques that can be more easily scaled in a homogenous and robust manner . Similarly, to minimize variability in patient outcomes, homogeneity in nanomedicine properties is critical and may necessitate improvements to both separation and characterization methods to ensure precision.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity can be exacerbated by scaling up from small scale bulk mixing conditions found in a laboratory to larger size volumes, especially as mixing environments vary with different types of processing equipment. To help alleviate these concerns, increasing attention in the nanomedicine field has turned to continuous manufacture processes such as microfluidic mixing and extrusion techniques that can be more easily scaled in a homogenous and robust manner . Similarly, to minimize variability in patient outcomes, homogeneity in nanomedicine properties is critical and may necessitate improvements to both separation and characterization methods to ensure precision.…”
Section: Discussionmentioning
confidence: 99%
“…PBAE polymers were synthesized as previously described (Tzeng et al, ; Wilson, Mosenia, et al, ). PBAE 4‐4‐6 used in this study was characterized via GPC to have M n 5,170 Da, M w 10,220 Da, and dispersity (D) 1.98, while PBAE 4–5‐39 was characterized to have M n 4,580 Da, M w 14,290 Da, and D 3.12.…”
Section: Resultsmentioning
confidence: 99%
“…Using a flowrate of 45 mL/h, flow inside the device reached a maximum Reynolds number of 125, which allowed for the self‐assembly of DNA‐containing PBAE nanoparticles without causing significant DNA shear. Using sucrose as a cryoprotectant, the nanoparticles exiting the microfluidic chip were allowed to directly drip into liquid nitrogen for flash freezing and lyophilization for long‐term storage . The lyophilized nanoparticles produced in this study showed no significant difference in transfection efficacy compared to freshly made nanoparticles after storage at −20°C for 3 months.…”
Section: Product Design Considerationsmentioning
confidence: 88%
“…To construct the polymeric nanoparticles, the PBAE polymer and the plasmid DNA are combined in the presence of acidic buffer to form nanoparticles via self‐assembly. Wilson et al recently reported on a microfluidic approach capable of rapid, mixing of PBAE solutions with plasmid DNA solutions to form PBAE nanoparticles as part of a continuous process . Using a flowrate of 45 mL/h, flow inside the device reached a maximum Reynolds number of 125, which allowed for the self‐assembly of DNA‐containing PBAE nanoparticles without causing significant DNA shear.…”
Section: Product Design Considerationsmentioning
confidence: 99%